Relationship between teaching quality factors and employability among Technology Management students - Amran Rasli; Tan Owee Kowang; Lim Kim Yew; How Wen Yen; Ong Choon Hee; Goh Chin Fei; Choi Sang Long (Institute of Advanced Engineering and Science, 2022)
Education system within higher education institution (HEI) is constantly evolved to enhance students’ employability in respond to the change of social-economy and technological revolution. Empirical research revealed that teaching quality is extremely important for the development of students’ employability attributes. Hence, one of the biggest challenges for HEI is to continuously improve teaching quality with the aim to enhance student employability. This study examined the influence of teaching quality on the employability of Technology Management students. Three important factors for teaching quality are identified from literature review comprising of learner quality, learning environment quality and content quality. This study used quantitative method to collect data via online questionnaire with 60 Technology Management students from a Business School within Malaysia responded. Data collected was analyzed using SPSS in term of normality, reliability, descriptive and Pearson correlation test. Finding from this study reveals that learning environment quality, content quality and learner quality are important, significant and positively correlated with employability. The main implication of this study is students’ employability could be assessed based on teaching quality directly instead of via students’ academic performance or employability attribute.